Electronic HRM in theory and practice - Bondarouk, Tanya, 1967-; Ruel, Huub.; Looise, Jan Kees, 1949- (Bingley, U.K. : Emerald, 2011)
Organizations have increasingly been introducing web-based applications for HRM purposes, and these are frequently labeled as electronic Human Resource Management (e-HRM). Much is expected of e-HRM in terms of improving the quality of HRM and increasing its contribution to company performance. Major investments are involved and are justified given the expectations that e-HRM will improve HRM quality in organizations by freeing staff from administrative loads. These beliefs originate from ideas about the endless possibilities of information technologies (IT) in facilitating HR practices, and about the infinite capacity of HRM to adopt IT. At the same time, it is not clear where e-HRM research should be positioned. Is it a new and substantial research area, or at the crossroads of other academic domains, such as Innovation Management, IT implementation, and/or HRM? Theoretical complexity has practical consequences for e-HRM projects and their management. The one-sided scholarly e-HRM works available fail to fully address this lack of clarity and, if anything, deepen the divisions between the various academic domains. To this end, we have been involved in a series of research projects, academic workshops, and conferences exploring the application of information technologies to various HR practices. Along with the Special Issues of the International Journal of HRM, International Journal of Technology and Human Interactions, and International Journal of Training and Development, this volume is a tangible outcome of three European e-HRM Academic Workshops (2006, 2008, 2010), and two International Workshops on Human Resource Management (2007 and 2008). Further, we gratefully acknowledge Graeme Martin, Martin Reddington, and Heather Alexander for their 2008 book on technology and transforming HR. By focusing on the theories and practices of technology in HRM in a range of international settings, it provided a foundation for our project and this volume and has, hopefully, allowed us to bring a greater focus to the theoretical developments within the field of e-HRM research. We hope that this book clarifies the need to crystallize a theoretical framework for e-HRM research, raises further questions, and supports discussions.
Introduction / Tanya Bondarouk, Huub Ru$1#0<(B, Jan Kees Looise -- ch. 1. Theoretical approaches to e-HRM implementations / Tanya Bondarouk -- ch. 2. Human resource information systems : an integrated research agenda / Huub Ru$1#0<(B, Rodrigo Magalh{u4865}s, Charles C. Chiemeke -- ch. 3.'Web mining' as a novel approach in e-HRM research / Stefan Strohmeier, Franca Piazza -- ch. 4. Linking HR strategy, e-HR goals, architectures, and outcomes : a model and case study evidence / Martin Reddington, Graeme Martin, Tanya Bondarouk -- ch. 5. A framework for the comparative analysis of HR shared services models / Tanya Bondarouk -- ch. 6.'Local universe' and uses of an HR Intranet : discursive results from the case of middle management / Karine Guiderdoni-Jourdain, Ewan Oiry -- ch. 7. Language issues in e-HRM implementation in the multinational firm / Jukka-Pekka Heikkil$1'X" (BAdam Smale -- ch. 8. e-Recruitment : from transaction-based practices to relationship-based approaches / Aurie Girard, Bernard Fallery -- ch. 9. Drivers of the adoption of online recuitment : an analysis using innovation attributes from diffusion of innovation theory / Emma Parry, Miguel R. Olivas-Luj.s
Keywords: Personnel management